The Relationship between Cardiovascular Autonomic Dysfunction and Ocular Abnormality in Chinese T2DM - Dandan Wang; Baiyu Shen; Chunrong Wu; Yanyan Xue; Yanjun Liu (Journal of Diabetes Research)
Objective. This study aims to explore the relationship between autonomic nerve dysfunction—assessed by cardiovascular autonomic neuropathy risk score (CAN-RS)—and ocular abnormality in Chinese type 2 diabetes mellitus (T2DM). Method. This is a cross-sectional study. A total of 335 subjects with T2DM were enrolled. The state of visual acuity, the lens, the vitreous, and the fundus were tested by professional ophthalmic instruments. The electrochemical skin conductance (ESC) of the hands and feet was measured by SUDOSCAN, from which a cardiovascular autonomic neuropathy risk score (CAN-RS) was calculated. Receiver operating characteristic (ROC) curves were drawn to evaluate the feasibility and accuracy of CAN-RS in diabetic oculopathy screening. Results. Abnormalities of the lens, vitreous, and fundus accounted for 7.8%, 5.1%, and 9.9%, respectively, in this study. The means of hands and feet ESC were higher than 60 μS, and CAN-RS was 33.1 ± 14.8%. In logistic regression analysis, CAN-RS was positively associated with lens (OR = 1.055, P<0.001) and vitreous (OR = 1.044, P<0.01) abnormality. The area under ROC to detect lens and vitreous abnormality was 0.713 and 0.725, respectively. Conclusion. CAN-RS, a cardiac autonomic nerve dysfunction index calculated by SUDOSCAN, may be a promising index for lens and vitreous abnormality screening in T2DM patients. Further studies are needed to confirm the conclusion.